Long‐Term Management of the Successful Adult Liver Transplant: A Patient‐Friendly Summary of the 2012 AASLD and AST Practice Guideline. Issue 3 (28th January 2022) - Shetty, Akshay; Kodali, Sudha
Abstract : Content available: Author Audio Recording